Industry 4.0 concepts and technologies: a bibliometric analysis - Lima, Faique Ribeiro; Gomes, Rogerio [UNESP] (Univ Estadual Campinas, Inst Geociencias, Dept Politica Cientifica & Tecn, 2020)
The general objective of this work is to evaluate characteristics of international scientific production in technologies associated with Industry 4.0. The methodology employed consists of two stages: (i) selection of technologies (terms) pointed out in the specific literature; (ii) the bibliometric analysis of scientific publications that contain the characteristic terms of Industry 4.0 existing in the Scopus database. The hypothesis adopted was that, as it is still an ongoing process, Industry 4.0 and its concepts are still under construction. Some of the conclusions of the work are: the countries that stand out the most are those that implemented national strategies related to the technologies of Industry 4.0, obtained, in the subsequent years, a wide growth in the number of publications; and, among the financing institutions, the governmental ones stand out in the sponsorship of scientific publications, especially the Chinese ones, proving the public effort.
Keywords: Advanced manufacturing; Bibliometric analysis; Industry 4.0; Innovation; Technology